Accuracy of Physicians Interpreting Photoplethysmography and Electrocardiography Tracings to Detect Atrial Fibrillation: INTERPRET-AF - Gruwez, Henri; Evens, Stijn; Proesmans, Tine; Duncker, David; Linz, Dominik; Heidbuchel, Hein; Manninger, Martin; Vandervoort, Pieter; Haemers, Peter; Pison, Laurent (Frontiers in Cardiovascular Medicine, 2021)
Aims This study aims to compare the performance of physicians to detect atrial fibrillation (AF) based on photoplethysmography (PPG), single-lead ECG and 12-lead ECG, and to explore the incremental value of PPG presentation as a tachogram and Poincaré plot, and of algorithm classification for interpretation by physicians. Methods and results Email invitations to participate in an online survey were distributed among physicians to analyse almost simultaneously recorded PPG, single-lead ECG and 12-lead ECG traces from 30 patients (10 in sinus rhythm (SR), 10 in SR with ectopic beats and 10 in AF). The task was to classify the readings as ‘SR’, ‘ectopic/missed beats’, ‘AF’, ‘flutter’ or ‘unreadable’. Sixty-five physicians detected or excluded AF based on the raw PPG waveforms with 88.8% sensitivity and 86.3% specificity. Additional presentation of the tachogram plus Poincaré plot significantly increased sensitivity and specificity to 95.5% (P<0.001) and 92.5% (P<0.001), respectively. The algorithm information did not further increase the accuracy to detect AF (sensitivity 97.5%, P=0.556; specificity 95.0%, P=0.182). Physicians detected AF on single-lead ECG tracings with 91.2% sensitivity and 93.9% specificity. Diagnostic accuracy was also not optimal on full 12-lead ECGs (93.9% and 98.6%, respectively). Notably, there was no significant difference between the performance of PPG waveform plus tachogram and Poincaré, compared to a single-lead ECG to detect or exclude AF (sensitivity P=0.672; specificity P=0.536). Conclusions Physicians can detect AF on a PPG output with equivalent accuracy compared to single-lead ECG, if the PPG waveforms are presented together with a tachogram and Poincaré plot and the quality of the recordings is high.